2000
DOI: 10.1110/ps.9.3.497
|View full text |Cite
|
Sign up to set email alerts
|

A “structural” water molecule in the family of fatty acid binding proteins

Abstract: A single water molecule~w135!, buried within the structure of rat intestinal fatty acid binding protein~I-FABP!, is investigated by NMR, molecular dynamics simulations, and analysis of known crystal structures. An ordered water molecule was found in structurally analogous position in 24 crystal structures of nine different members of the family of fatty acid binding proteins. There is a remarkable conservation of the local structure near the w135 binding site among different proteins from this family. NMR cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 37 publications
0
32
1
1
Order By: Relevance
“…These observations are in contrast with data obtained on rI-FABP both from crystal (Likic et al, 2000) and MD data analyses (Bakowies and van Gunsteren, 2002a). The authors identified, respectively, approx.…”
Section: Resultscontrasting
confidence: 89%
“…These observations are in contrast with data obtained on rI-FABP both from crystal (Likic et al, 2000) and MD data analyses (Bakowies and van Gunsteren, 2002a). The authors identified, respectively, approx.…”
Section: Resultscontrasting
confidence: 89%
“…A conserved structural water molecule in the FABP family has also been reported; P2 was not analyzed in that study [57]. This water is located in a pocket close to the protein external surface, in a wedge formed by the loop between β-strands D and E. From the human P2 structure, it is evident that this water molecule is also present, being H-bonded to the backbone NH group of Val84 and the carbonyl oxygens of Lys65 and Gln68 (data not shown).…”
Section: Resultsmentioning
confidence: 93%
“…Prendergast's group21, 36 has extensively studied a conserved, internal solvent site in fatty‐acid binding proteins using NMR, molecular dynamics simulations, and analysis of crystal structure data. In our study, this site corresponded to the top peak in the water distribution map (62σ), and the site had 100% conservation [Table II, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…One hypothesis is that structurally and functionally important water molecules occupy solvent sites that are highly conserved among proteins sharing a common three‐dimensional fold or active site structure. Conserved solvent sites have been examined only in a few protein families, such as fatty‐acid binding proteins,21 cytochrome c ,22 lectins,23 phospholipase A 2 ,24 ribonucleases,25 Rossmann dinucleotide‐binding proteins,3 serine proteases,13, 26, 27 and parvalbumins 28…”
Section: Introductionmentioning
confidence: 99%